The struggles of call-center workers in Pernambuco and their resistance strategies - Costa, Rafaela Ribeiro Saraiva da; Silva, Maria das Graças e (Argumentum, 2022)
This study analyzes the individual and collective resistance strategies developed by call-center workers in the state of Pernambuco against work intensification. The objective is to understand the relationship between the Union and the operators in the process of daily struggle and in the construction of confrontation strategies. Methodologically, the research has a bibliographic and field character with semi-structured interviews with four female workers and a Union leader. It observes that the call-center workers make themselves available every day for confrontation and are building creative, spontaneous, and day-by-day strategies, these do not, however, have a political character owing to the absence of a continuous process of political education, this attests to the distance between call-center workers and their Union representation in Recife.